Impact of unbalanced minor route versus major route karyotypes at diagnosis on prognosis of CML - Fabarius, Alice; Kalmanti, Lida; Dietz, Christian T.; Lauseker, Michael; Rinaldetti, Sebastien; Haferlach, Claudia; Goehring, Gudrun; Schlegelberger, Brigitte; Jotterand, Martine; Hanfstein, Benjamin; Seifarth, Wolfgang; Haenel, Mathias; et al. (Annals of Hematology, 2015)
Major route additional cytogenetic aberrations (ACA) at diagnosis of chronic myeloid leukaemia (CML) indicate an increased risk of progression and shorter survival. Since major route ACA are almost always unbalanced, it is unclear whether other unbalanced ACA at diagnosis also confer an unfavourable prognosis. On the basis of 1348 Philadelphia chromosome-positive chronic phase patients of the randomized CML study IV, we examined the impact of unbalanced minor route ACA at diagnosis versus major route ACA on prognosis. At diagnosis, 1175 patients (87.2 %) had a translocation t(9;22)(q34;q11) and 74 (5.5 %) a variant translocation t(v;22) only, while a loss of the Y chromosome (-Y) was present in addition in 44 (3.3 %), balanced or unbalanced minor route ACA each in 17 (1.3 %) and major route ACA in 21 (1.6 %) cases. Patients with unbalanced minor route ACA had no significantly different cumulative incidences of complete cytogenetic remission or major molecular remission and no significantly different progression-free survival (PFS) or overall survival (OS) than patients with t(9;22), t(v;22), -Y and balanced minor route karyotypes. In contrast, patients with major route ACA had a shorter OS and PFS than all other groups (all pairwise comparisons to each of the other groups: p <= 0.015). Five-year survival probabilities were for t(9;22) 91.4 % (95 % CI 89.5-93.1), t(v; 22) 87 % (77.2-94.3), -Y 89.0 % (76.7-97.0), balanced 100 %, unbalanced minor route 92.3 % (72.4-100) and major route 52.2 % (28.2-75.5). We conclude that only major route, but not balanced or unbalanced minor route ACA at diagnosis, has a negative impact on prognosis of CML.
EVALuna2:25723